(untitled) (Research, Society and Development, 2021)
Gastric ulcer is a disease that affects a large portion of the world population, with a prevalence of 2.4% in the Western population and annual incidence rates of 0.10% to 0.19%, with a high cure rate, but with a high recurrence rate. The aim of this research is to perform a literature review on the gastroprotective potential of the essential oil of Lippia gracilis Schauer. To this end, an integrative review study was carried out, which selected 26 scientific articles found in virtual platforms that approached the proposed theme. Based on the established criteria, the literature suggests that the essential oil of Lippia gracilis Schauer is a compound with several biological activities, including some already described in the literature, however, its gastroprotective potential is still lacking many evidences in the literature. The findings show that the EO of L. gracilis can delay and bring an improvement in the degree of involvement by the ulcerative disorder. However, new scientific approaches are necessary to better elucidate the effect of this oil, which can then become an additional therapeutic method for cases of gastric lesions.